Effect of Solvent Polarity and Extraction Method on Phytochemical Composition and Antioxidant Potential of Corn Silk - Nawaz, Haq; Aslam, Momna; Muntaha, Sidra Tul (Free Radicals and Antioxidants)
Objectives: Corn silk is an underutilized part of corn which possesses great medicinal importance. The present study was planned to determine the phytochemical composition and antioxidant potential of corn silk extracts, obtained by different extraction methods using a series of solvents with increasing polarity. Methods: Three extraction methods 1) individual extraction in each solvent, 2) consecutive extraction in solvents of increasing polarity and 3) consecutive extraction of crude methanolic extract in solvents of increasing polarity and a series of five solvents with increasing polarity were used for extraction of phytochemicals. The extracts were analyzed for phytochemical composition and antioxidant potential. Results: Corn silk was found to contain a variety of bioactive phytochemical compounds including phenolic acids, flavonoids, ascorbic acid, tannins and cardiac glycosides. The corn silk phytochemicals were extracted more in high polarity solvents which showed comparatively good phytochemical composition and strong antioxidants potential. Regression analysis of experimental data showed a polarity dependent increase in extraction yield and phytochemical content and free radical scavenging capacity of extracts obtained by various extraction methods. Conclusion: The water extract obtained by individual extraction showed a comparatively high extraction yield and phytochemical content while that obtained by consecutive extraction of crude methanolic extract showed high ability to scavenge free radicals. The study advocates the corn silk as a good source of antioxidant phytochemicals and suggests the use of polar solvents and individual extraction method for extraction of corn silk phytochemicals.
Keywords: Antioxidant potential; Corn silk; Extraction methods; Free radical scavenging capacity; Phytochemical composition; Solvent polarity